Application of Gaba-Gaba Egg Rack Bio-Composite as Material Wall Meeting Room Acoustics - Sabaruddin, Sabaruddin; Samad, Sudarman; Marasabessy, Firdawaty; Muhammad, Asri A (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bio composite materials are a combination of two or more natural polymer materials or biofiber (natural fibers) which can be degraded as reinforcement and polymer or matrix. Natural fibers generally have the ability to absorb sound well and have basic properties as composite reinforcements. If a wave hits a material, the wave can be straightened, reflected and absorbed. The ability of composite structures to absorb sound can be used to reduce noise levels. This research models a combination of egg rack waste mixed with sago leaf stem (gaba-gaba) waste as a bio-composite material for room acoustic panels. This research uses a material modeling engineering method which is a pure experiment, with the stages of making test samples based on fixed variables and measurable variables and then testing to obtain the material absorption coefficient, then the test results are based on the specified variables, then applying the material to the meeting room. After that tested the acoustic level of the room, especially the meeting room.